2014
DOI: 10.1038/ncomms5549
|View full text |Cite
|
Sign up to set email alerts
|

A single locus confers tolerance to continuous light and allows substantial yield increase in tomato

Abstract: An important constraint for plant biomass production is the natural day length. Artificial light allows for longer photoperiods, but tomato plants develop a detrimental leaf injury when grown under continuous light-a still poorly understood phenomenon discovered in the 1920s. Here, we report a dominant locus on chromosome 7 of wild tomato species that confers continuous light tolerance. Genetic evidence, RNAseq data, silencing experiments and sequence analysis all point to the type III light harvesting chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 68 publications
(83 reference statements)
4
98
0
Order By: Relevance
“…In CLexposed plants, however, cytokinin treatment largely prevented the CL-induced injury. To evaluate further the effect of CL on cytokinin signaling, transcriptome contrasts between A131 and CLT (Velez-Ramirez et al 2014) were mapped to the tomato Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway for 'Plant hormone signal transduction' (sly04075). Supplementary Fig.…”
Section: Cytokinin Diminishes Continuous Light-induced Injury In Tomatomentioning
confidence: 99%
See 3 more Smart Citations
“…In CLexposed plants, however, cytokinin treatment largely prevented the CL-induced injury. To evaluate further the effect of CL on cytokinin signaling, transcriptome contrasts between A131 and CLT (Velez-Ramirez et al 2014) were mapped to the tomato Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway for 'Plant hormone signal transduction' (sly04075). Supplementary Fig.…”
Section: Cytokinin Diminishes Continuous Light-induced Injury In Tomatomentioning
confidence: 99%
“…Nevertheless, a role for carbohydrate accumulation cannot be discarded. A transcriptomics study showed that the Gene Ontology (GO) term 'Carbohydrate metabolic process' is significantly enriched in differentially regulated genes in CL-sensitive tomato plants exposed to CL (compared with a 16 h photoperiod) and in CL-tolerant plants under CL (compared with CL-sensitive plants) (Velez-Ramirez et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…pruning of fruit and leaves) are often applied to investigate the balance of source-reservoir plants (Matsuda et al, 2011). Crop growth models can be used to measure the power source and the bottom (Wubs et al, 2009). In this model, the strength of the bottom of the organ that develops is determined by the level of potential growth (i.e.…”
Section: Introductionmentioning
confidence: 99%